Diseño de propuesta de valor basada en una experiencia para el colaborador desde una perspectiva del modelo 'EFR' en la empresa veolia aguas de Tunja SA -ES.P. (2023)
The company Veolia Aguas de Tunja SA -ES.P, (giving rise and abbreviation from now on to mention VEOLIA.), was certified with the "Family Responsible Company" (EFR) model of the Más Familia Foundation in 2013, with a Focus on balancing personal, work and family balance to enhance work performance. After a constant process of evolution, VEOLIA seeks to obtain A+ and A Plus certification, reflecting an exceptional commitment to conciliation and the effective implementation of measures that benefit employees.